Kajian Mengenai Faktor-faktor yang dapat Mendorong Peningkatan Product Holding Ratio - Armalisa Dwi Yani; Gusti Oka Widana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Research examines the factors that can drive an increase in the Product Holding Ratio at Bank Syariah Indonesia, especially in the Jambi branch. The Product Holding Ratio is an important indicator in assessing the performance of banking products, which reflects how many products are owned by customers. This study uses a qualitative method with in-depth interviews with various informants, including branch managers and brand managers, to identify factors that contribute to an increase in the Product Holding Ratio. The results of the study indicate that there are several key factors that can drive an increase in the Product Holding Ratio, including sharia financial literacy, service quality, and effective marketing strategies. Low financial literacy in the community is a major challenge, where only around 38% of the community understands financial products well. Therefore, intensive financial education through seminars, workshops, and social media is needed to improve customer understanding of sharia products. In addition, good service quality also contributes significantly to customer loyalty. Research shows that customers who are satisfied with the services provided tend to use more products. The application of digital technology in banking services is also an important factor, where the use of user-friendly mobile banking applications can increase customer convenience in accessing services. Effective marketing strategies, including digital marketing and collaboration with local communities, are also a major focus in increasing the Product Holding Ratio. By establishing partnerships with educational institutions and community organizations, banks can expand their reach and increase public trust in the products offered. Overall, this study provides in-depth insight into the factors that can increase the Product Holding Ratio at Bank Syariah Indonesia, Jambi branch. The results of this study are expected to be a reference for bank management in formulating more effective strategies to increase the Product Holding Ratio and strengthen the bank's position in the Islamic banking market.